Workers' Rights on Omnibus Law Seen from Islamic Perspective in The Context of Maqasid Syariah - Triwasono , Soni Hari; Imron , Ali; Rohmy , Atikah Mardhiya (LPPPM STAI Darul Hikmah Bangkalan, 2022)
This article discusses labor rights in the laws and regulations in Indonesia. In particular, regarding the rights of workers who are approaching retirement age. There are also laws that are the subject of discussion, namely Law Number 13 of 2013 concerning Manpower and Law Number 11 of 2020 (Omnibus Law). All of this is also discussed from an Islamic perspective. The focus is on the Maqasid Sharia concept, as an effort to protect religion, life, wealth/property, intellect/mind, and descendants or the next generation, from every individual on earth. Maqasid sharia always relies on the principles of justice and the welfare of the people. This study uses a qualitative method with a literature study approach. The results of this study indicate that there are a number of problems in the application of laws relating to employment in Indonesia. Especially, in the new law, namely, the 2020 Omnibus Law. The problems referred to include, among other things, the unclear working contract period, changes to the minimum wage provisions, complicated outsourcing rules, the concept of termination of employment, and ambiguous leave terms. The government must pay attention to these findings. Viewed from the perspective of Maqasid Syariah, the lack of clarity on the term of the employment contract, the provisions of the minimum wage, outsourcing, and termination of employment can be classified as endangering one's financial aspects (wealth). While the issue of leave often has a negative impact on a person's physical and mental health (life and mind). This study is expected to have theoretical benefits in the fields of employment, public policy, and Omnibus Law. There is also a practical benefit for readers is to open up insight about the problems around, in connection with the Omnibus Law. Keywords: Labor Rights, Public Policy, Maqasid Syariah, Omnibus LawÂ Â Â